Invasive dermatophyte infection with Trichophyton interdigitale is associated with prurigo‐induced pseudoperforation and a signal transducer and activator of transcription 3 mutation4. (5th March 2018) - Simpson, J.K.; Fröbel, P.; Seneviratne, S.L.; Brown, M.; Lowe, D.M.; Grimbacher, B.; Fliegauf, M.; Fearfield, L.
Summary: Invasive dermatophyte infection, with extension beyond the dermis, in immunocompetent hosts is exceptionally rare. Dermatophytes are keratinophilic and are usually confined to the stratum corneum, hair and nails. Susceptibility to dermatophyte infections is incompletely understood, but inherited mutations in key signalling pathways of the innate immune system have been identified. We report the first case of an invasive dermatophyte infection associated with abrupt onset of a prurigo‐induced pseudoperforation and a loss‐of‐function mutation in signal transducer and activator of transcription 3 (STAT3). Abstract : What's already known about this topic? Invasive dermatophyte infections are exceptionally rare in immunocompetent individuals. Inherited genetic mutations in innate immune system signalling pathways may predispose to invasive dermatophyte infections. Signal transducer and activator of transcription 3 (STAT3) mutations are associated with autosomal dominant hyper‐IgE syndrome and susceptibility to fungal infections, particularly with Candida . What does this study add? STAT3 mutations may predispose to invasive dermatophyte infection. This susceptibility to infection may be due to defective T helper 17 signalling. Pseudoperforation secondary to prurigo may be associated with underlying fungal infections. Linked Comment: Wang and Li. Br J Dermatol 2018;179 :567–568 . Plain language summary available online